THE EFFECT OF FAMILY SUPPORT ON STUDENTS' EMOTIONAL INTELLIGENCE THROUGH SELF-COMPASSION MEDIATION AT SMP NEGERI 34 MEDAN - Rimelda Tarigan; Salamiah Sari Dewi; Amanah Surbakti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study was to determine and test empirically To determine whether the role of Self-compassion mediation in the influence of family support on emotional intelligence in students This study uses a quantitative method, with a population of 389 and a sample of 389. The sampling technique used is the total sampling technique. The data analysis technique used is structural equation modeling (SEM). After testing the hypothesis, the results obtained Family support has an effect on Emotional Intelligence, with a path coefficient value of 0.623, and significant, with a p value <0.001. Furthermore, family support has an effect on Self-compassion, with a path coefficient value of 1.133, and significant, with a p value <0.001. then, self-compassion has an effect on Emotional Intelligence, with a path coefficient value of 0.358, and is significant, with a p value <0.001. The indirect effect of family support on Emotional Intelligence, through self-compassion is 0.462. It is known that self-compassion significantly mediates the effect between family support and Emotional Intelligence.